2018
DOI: 10.1002/anie.201801498
|View full text |Cite
|
Sign up to set email alerts
|

Charge Neutralization Drives the Shape Reconfiguration of DNA Nanotubes

Abstract: Reconfiguration of membrane protein channels for gated transport is highly regulated under physiological conditions. However, a mechanistic understanding of such channels remains challenging owing to the difficulty in probing subtle gating-associated structural changes. Herein, we show that charge neutralization can drive the shape reconfiguration of a biomimetic 6-helix bundle DNA nanotube (6HB). Specifically, 6HB adopts a compact state when its charge is neutralized by Mg2+; whereas Na+ switches it to the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 38 publications
2
32
0
1
Order By: Relevance
“…SAXS data first suggested an unexpected slight deformation of TDN structures in solution. By fitting the SAXS data with a combination of normal mode analysis (NMA) and fast-SAXS-pro program, 28,29 we found that the revised TDN molecular structure showed a slight twist, which matched well with the experimental results (c 2 = 7.1, Figures 3A and 3B). The average distance between two base pair increased from 3.40 to 3.55 Å , suggesting stretching of DNA molecules due to their intrinsic elasticity.…”
Section: Saxs and MD Analysis Of The Mechanism For Cap Crystallizationsupporting
confidence: 77%
See 1 more Smart Citation
“…SAXS data first suggested an unexpected slight deformation of TDN structures in solution. By fitting the SAXS data with a combination of normal mode analysis (NMA) and fast-SAXS-pro program, 28,29 we found that the revised TDN molecular structure showed a slight twist, which matched well with the experimental results (c 2 = 7.1, Figures 3A and 3B). The average distance between two base pair increased from 3.40 to 3.55 Å , suggesting stretching of DNA molecules due to their intrinsic elasticity.…”
Section: Saxs and MD Analysis Of The Mechanism For Cap Crystallizationsupporting
confidence: 77%
“…The data were further analyzed by ATASAS 2.7.2 package and Fast-SAXS-Pro. 29 Briefly, the fitting was achieved by initially performing NMA sampling on MD-generated models, and then structural energy minimization, followed by evaluation via goodness-of-fit (denoted by c 2 ) between theoretical and experimental scattering data, where each theoretical SAXS curve was calculated by fast-SAXS-pro, which specially accounts for the hydration characteristic of DNA. The fitting results were also validated by CRYSOL and FoXS.…”
Section: Saxs Characterizationmentioning
confidence: 99%
“…In summary, we carried out an in situ structural determination of segmented DNA nanotubes through joint experimental and theoretical studies. In particular, our pioneering SAXS studies on assembled DNA nanotubes have provided useful information for the study of DNA nanostructures with conformations more complex than those investigated in previous SAXS studies on uniform DNA nanostructures . This work should also shed light on programmable length control of various DNA nanotubes.…”
Section: Methodsmentioning
confidence: 85%
“…A ligand‐controlled transporter was demonstrated by using DNA strand displacement to control the opening and closing of a DNA nanopore (Figure h). [21a] Liu et al used charge neutralization to drive the shape reconfiguration of a biomimetic DNA nanochannel . Fisher et al used DNA nanopores to confine and organize disordered nucleoporins that mimicked the central transport channel of nuclear pore complexes .…”
Section: Dna Nanostructures‐confined Lipid Membrane and Transportersmentioning
confidence: 99%